Undergraduate students’ perceptions and preferences toward online learning in the post-pandemic era - Lestariyanti, Elina; Tauhidah, Dian (Jurnal Pembangunan Pendidikan: Fondasi dan Aplikasi, 2025)
The transition to post-pandemic education has encouraged higher education institutions to reconsider the role of online learning in teaching and learning processes. This study aims to examine undergraduate students’ perceptions and preferences regarding the implementation of online learning in the post-pandemic era. A quantitative descriptive approach was employed involving 72 biology education students at UIN Walisongo Semarang who had experienced online learning during the COVID-19 pandemic. Data were collected using a Likert-scale questionnaire measuring students’ perceptions and preferences toward online learning. The data were analyzed using descriptive statistics and t-test analysis. The findings indicate that students’ perceptions of online learning are influenced by several factors, including internet connectivity, learning environment, instructional techniques, and teaching methods. Although students generally prefer offline learning, they still consider online learning as a complementary or alternative learning mode. These findings suggest that hybrid or flexible learning models may be more appropriate for post-pandemic higher education to accommodate students’ learning preferences and technological readiness.